Shareholders Lawsuit: Fraud on Minority Law Enforcement to Invent Corrective Justice During the Covid-19 - Yusro, Mochammad Abizar (Law Research Review Quarterly, 2022)
The purpose of this study is to analyse and provide recommendations for national law, related to law enforcement in violations against minorities (fraud on minorities) shareholders to create corrective justice during the covid-19 period. Minority Shareholders are a group that is classified as vulnerable to actions that can result in losses. For this reason, law enforcement efforts against Minority Shareholder fraud are needed, to provide legal protection and recovery of losses in order to create corrective justice. This research method is descriptive by using the type of juridical-normative research. The type of approach used is a statutory approach and a conceptual approach. The results of this study describe the rights of shareholders given by laws and regulations, which can be used to carry out legal remedies based on corrective justice when fraud is on a minority. The legal effort began with a shareholder lawsuit consisting of two mechanisms, namely derivative action and direct action from shareholders which has been accommodated in Law Number 40 of 2007 concerning Limited Liability Companies. However, this effort is commonly used and has several weaknesses, one of which is the absence of specification rules related to the procedures for implementing it.